Correction: TiO2/g-C3N4 heterojunction hollow porous nanofibers as superior visible-light photocatalysts for H2 evolution and dye degradation. (4th January 2022) - Liu, Jing; Li, Dianming; Liu, Xiaofeng; Zhou, Jie; Zhao, Hong; Wang, Nü; Cui, Zhimin; Bai, Jie; Zhao, Yong
Abstract : Correction for 'TiO2 / g -C3 N4 heterojunction hollow porous nanofibers as superior visible-light photocatalysts for H2 evolution and dye degradation' by Jing Liu et al., New J. Chem., 2021, 45, 22123–22132, DOI: ; 10.1039/d1nj04390k .